High-Performance Work Practices and Interpersonal Relationships: Laissez-Faire Leadership as a Risk Factor - Salin, Denise; Baillien, Elfi; Notelaers, Guy (Frontiers in Psychology, 2022)
Although high-performance work practices (HPWPs) have been shown to increase organizational performance and improve employee attitudes, it still remains unclear how they impact interpersonal relations in the workplace. While some argue that HPWPs lead to better interpersonal relations, others fear that HPWPs may increase competition and uncivil and abusive behaviors. In response to this, our aim is to examine whether and when HPWPs are associated with increased levels of competition and thereby more incivility. Given recent interest in how HR practices and leadership may interact to produce certain outcomes, we study laissez-faire leadership as a possible moderator. A survey was conducted in Belgium (n=374), and a mediated moderation analysis using SEM performed using Mplus. The results suggest that in the absence of laissez-faire leadership, HPWPs are associated with less incivility, thus suggesting better interpersonal relations. However, the results also show that HPWPs may lead to increased competition and thereby somewhat more incivility, under conditions of laissez-faire leadership. The results thus point to the importance of studying interactions between HR practices and leadership in trying to understand employee outcomes. In terms of practical implications, the results suggest that investing in HPWPs may reduce incivility and thereby improve relationship well-being. However, HPWPs need to be combined with active leadership to avoid undesirable negative consequences.